Let's solve your equation step-by-step.
−66.17738=6.618(4.3x+1.1)−7.1(x−6.8)
Step 1: Simplify both sides of the equation.
−66.17738=6.618(4.3x+1.1)−7.1(x−6.8)
−66.17738=(6.618)(4.3x)+(6.618)(1.1)+(−7.1)(x)+(−7.1)(−6.8)(Distribute)
−66.17738=28.4574x+7.2798+−7.1x+48.28
−66.17738=(28.4574x+−7.1x)+(7.2798+48.28)(Combine Like Terms)
−66.17738=21.3574x+55.5598
−66.17738=21.3574x+55.5598
Step 2: Flip the equation.
21.3574x+55.5598=−66.17738
Step 3: Subtract 55.5598 from both sides.
21.3574x+55.5598−55.5598=−66.17738−55.5598
21.3574x=−121.73718
Step 4: Divide both sides by 21.3574.
21.3574x
21.3574
=
−121.73718
21.3574
x=−5.7